Geochronology of the Batagay Megaslump in East Siberia: B19-LU luminescence dating data sets and R scripts - Mittelstraß, Dirk; Fuchs, Margret C.; Lauer, Tobias; Wetterich, Sebastian; Kizyakov, Alexander; Opel, Thomas (Zenodo, 2024)
To improve the geochronology of the ancient permafrost deposits exposed in the headwall of the Batagay Megaslump in East Siberia (67.58°N, 134.77°E), we estimated the age of frozen sediments with luminescence dating and supplemented the results with other dating approaches and stratigraphical interpretation.